Protein contents and antioxidant properties of pleurotus ostreatus cultivated on tea and espresso wastes - Ayşenur Yılmaz; Sibel Yıldız; Ceyhun Kılıç; Zehra Can (International Journal of Secondary Metabolite)
In this study, Pleurotus ostreatus was cultivated on tea (Camellia sinensis) and espresso wastes. Tea wastes were used in two forms; sterilized or non-sterilized. Then, total phenolic, flavonoid, condensed tannin contents, ferric reducing/antioxidant capacity (FRAP) and 2,2-diphenyl-1-picryhydrazyl (DPPH) free radical scavenging were used as antioxidant determinants and also protein content were investigated in these mushrooms’ methanolic extracts. Same measurements were determined in mushrooms’ growing medium except protein content. The highest protein content (20.89%) was found in non-sterilized tea wastes. The highest total phenolic (1.460±0.012 mg GAE/g), total flavonoid (0.120±0.005 mg QE/g), condensed tannin (0.877±0.011 mg CE/g) and the lowest scavenging of free radical activity (17.190±0.001 mg/mL) were determined in sterilized tea wastes. The highest ferric reducing antioxidant power (8.498±0.089 μmolFeSO4.7H2O/g) were determined in espresso wastes. Additionally, there was no statistically significant difference between the sterilized and non-sterilized substrates for the total yield and biological efficiencies. In this case, it can be said that the kinds of substrates and their usage forms are very important in terms of energy savings especially does not require sterilization like tea wastes. Consequently, tea and espresso wastes can be used as a beneficial source of substrate material for Pleurotus ostreatus mushroom cultivation.